Fatal case of hemolytic-uremic syndrome in an adult due to a rare serogroup O91 Entero hemorrhagic Escherichia coli associated with a Clostridium difficile infection. More than meets the eye - Thomas Guillard; Anne Limelette; Elisabeth Le Magrex-Debar; Alain Wynckel; Malika Gouali; Patricia Mariani-Kurkdjian; Charlotte Guyot-Colosio; Christophe de Champs (International Journal of Infectious Diseases, 2015)
Hemolytic-uremic syndrome due to enterohemorrhagic Escherichia coli, belonging to serogroup O91 has rarely been described. We report here a case of post-diarrheal HUS due to EHEC O91 in an elderly patient for whom diagnosis was delayed given a previously diagnosed C. difficile infection. This case highlights the usefulness of Shiga-toxin detection.